Eliciting Preferences in Dentistry with Multiattribute Stated Preference Methods: A Systematic Review. (October 2018) - Barber, S.; Pavitt, S.; Khambay, B.; Bekker, H.; Meads, D.
Background: Preference experiments are used to understand how patients and stakeholders value aspects of health care. These methods are gaining popularity in dentistry, but quality and breadth of use have not been evaluated. Objectives: To describe multiattribute stated preference experiment use in dentistry through illustration and critique of existing studies. Data Sources: Systematic literature search of PubMed, Econlit and Ovid for Medline, Embase, PsychINFO, PsychARTICLES, and All EBM Reviews, as well as gray literature. Study Eligibility: Multiattribute stated preference experiments eliciting preferences for dental service delivery, treatments, and oral health states from the perspective of patients, the public, and dental professionals. Outcomes of interest were preference weights and marginal rates of substitution. Study selection was independently performed by 2 reviewers. Appraisal: Ten-point checklist published by the International Society of Pharmacoeconomics and Outcomes Research was used for quality assessment. Synthesis: Descriptive analysis. Results: Searches identified 12 records published between 1999 and 2015, mostly in nondental academic journals. Studies were undertaken in high-income countries in Europe and the United States. The studies aimed to elicit preference for service delivery, treatment, or oral health states from the perspective of the patients, dentists, or the public via discrete choice experiment methods. The quality scores for the studies ranged from 53% to 100%. Limitations: A detailed description and critique of stated preference methods are provided, but it was not possible to provide synthesized preference data. Conclusions: Multiattribute stated preference experiments are increasingly popular, but understanding the methods and outputs is essential for designing and interpreting preference studies to improve patient care. Patient preferences highlight important considerations for decision making during treatment planning. Valuation of health states and estimation of willingness-to-pay are important for resource planning and allocation and economic evaluation. Preference estimates and relative value of attributes for interventions and service delivery inform development and selection of treatments and services (PROSPERO 21.3.17: CRD42017059859). Knowledge Transfer Statement: Understanding patient, professional, and public preferences is fundamental for evidence-based decision making and treatment delivery. Preference elicitation methods can be used to estimate the value given to health states, service delivery, individual treatments, and health outcomes. By describing and appraising the methodology and application of multiattribute stated preference experiments in dentistry, this review provides an essential first step to wider use of well-designed, high-quality preference elicitation methods.